Coronavirus Disease 2019 (COVID-19) and Its Implications for Economic Security in the Republic of Indonesia-Papua New Guinea Border Market Area - Tambunan, Edwin Martua Bangun; Lantang, Floranesia (Jurnal Hubungan Internasional, 2022)
The COVID-19 pandemic spread to the Indonesia-Papua New Guinea (PNG) border poses a real threat to people living in the region. As a consequence of this pandemic, the Transnational Border Post (PLBN) and the border market have been temporarily closed since January 2020. This article aims to analyze the implications of COVID-19 on the economic security of the people at the RI-PNG border and the responses of two countries, particularly Indonesia, toward the economic security threats in the border region. This article was developed from qualitative descriptive research using field research methods. Data were collected through interviews and observations and supported by secondary data. This study revealed that the short-term implications of COVID-19 on economic security existed in the form of income reduction, even income loss, due to the closure of cross-border access. Income reduction may lead to the emergence of medium-term implications in the form of unemployment and debt. If there is no solution, the long-term implications may exist in the form of widespread poverty in the RI-PNG border area.